THE PLEA BARGAIN AGREEMENT - Mihai Daniel ONIȘOR (Challenges of the Knowledge Society, 2015)
Alongside major changes in Romanian criminal law, the plea bargain agreement gave a new approach on the mechanisms of criminal procedure in national law, thus creating a series of problems and divergent interpretations of the content and limits of this mechanism in solving criminal litigation. What motivated us in our scientific analysis was the novelty of the issues that arose both in the doctrine and interpretation of the legal provisions and in the practice of prosecution offices and national courts, the high impact that the new proceedings can have on criminal policy and the need for clear and efficient provisions that can ensure legal certainty. Our paper is divided in four major parts: the nature and object of the agreement, the conditions of plea bargain, the prosecutorial phase, court validation and appeal procedure, in each of these sections taking into account the legal provisions, analyzing working hypothesis, identifying probable issues and problems and providing our opinion on possible solutions. Our findings prove the fact that the novelty aspect of this procedure determined a number of gaps in the law, aspects that can dramatically influence the result of the criminal case and the guarantees that the parties have in criminal law. Moreover it will underline the unclear provisions that make the new law inapplicable in certain cases and leave a number of situations without any lawful solution.